Infant feeding practices in the Saharawi refugee camps Algeria, a cross-sectional study among children from birth to six months of age. Issue 1 (December 2016) - Aakre, Inger; Lilleengen, Anne; Lerseth Aarsand, Marie; Strand, Tor; Barikmo, Ingrid; Henjum, Sigrun
Abstract Background Appropriate breastfeeding and infant feeding practices are crucial to a child's growth and development. The objective of this paper is to describe breastfeeding and general feeding practices and the nutrition status among children from birth to 6 months of age, in the Saharawi refugee camps located in Algeria. Methods A cross-sectional study was carried out among 111 lactating mothers with infants from birth to 6 months of age. Data regarding breastfeeding practices and a 24 h dietary recall for the infants were collected to assess the World Health Organization's (WHO) indicators for infant and young child feeding. For exclusive and predominant breastfeeding, age disaggregation for each month was applied to the data. Background characteristics from the mothers and infants were collected, together with anthropometrical measures. We explored predictors for breastfeeding and nutrition status in multiple regression models. Results In total 13.8%, 8.2% and 16.5% of the infants were stunted, wasted and underweight, respectively. Approximately 65% initiated breastfeeding within 1 h after birth and 11.7 and 21.6% were exclusively or predominantly breastfed less than 6 months. The most commonly given solid foods were dates (27.0%) and bread (10.8%). In multiple regression models, initiation of breastfeeding within 1 h after birth gave increased probability of exclusive or predominant breastfeeding. Giving birth at home as opposed to in a hospital and increasing number of children gave increased probability of initiating breastfeeding early. Exclusive or predominant breastfeeding seemed to protect against underweight and wasting. Conclusions Exclusively or predominant breastfeeding was low among Saharawi refugee infants. Wasting and underweight was common and more likely to occur if the infants were not exclusively or predominantly breastfed. These findings support the current international breastfeeding recommendations, and suggest that there is an urgent need for promoting infant feeding practices in the Sahara refugee camps.